Peculiarities of cytokine type of regulation of immune answer in women with ovarian endometriomas - Shapoval, O. S.; Vorontsova, L. L. (Zaporozhye Medical Journal, 2017)
The problem of improving the treatment of endometrioid ovarian cysts is actual. The aim of the work was to reveal the features of the cytokine type of regulation of the immune response in women with ovarian endometriomas. Materials and methods. 100 women of reproductive age were examined (control group – 50 healthy women, the main one – 51 patients with ovatian endometriomas with different parity). General clinical examination, study of the immune status, bacteriological study of the vaginal discharge were conducted. Statistical processing of the obtained data was carried out using computer programs STATISTICA package (StatSoft Statistica v.6.0). Results. In the spectrum of microorganisms isolated from the vagina, G- and G+ bacteria (E. coli, Ent. Faecalis, Staphylococcus, Streptococcus coagulo-negative and coagulo-positive), fungi of the genus Candida were present. In all patients of the main group, a conditionally pathogenic flora, represented by Ent. faecalis was sown in 80 % of cases. – 107 CFU/ml, there was a decrease in the intolerance of colonization of Lactobacillus spp. In patients with infertility and nulliparity, a decrease in the functional activity of neutrophils at the digestion stage was noted. The indices of the phagocytic number of neutrophils indicated incompleteness of phagocytosis against the background of the depleted functional-metabolic reserve, the parameters of the bactericidal system were reduced. In women giving birth, the functional activity of neutrophils did not change, there was a decrease in digestive capacity against the background of the preserved functional metabolic reserve. In the group of nulliparous women, a Th2/Th1 type of immune response with a predominance of Th2 type was observed (an increase in the production of IL-4, IL-6, TNF-α in the blood serum was noted). When infertility, a Th1/Th2 type of immune response was observed with a predominance of the Th1 type (an increase in the content of TNF-α and IF-γ, IL-6, IL-10, IL-4 and IL-12). In the group of women giving birth, a Th2-type of immune response was observed (an increase in IL-4, IL-6, IL-10, IL-12, TNF-α and IF-γ). Conclusions. The change in the state of the vaginal microbiocenosis leads to the formation of dysfunction of the immune system, in particular the cytokine type of regulation. An increase of the level of cytokines and a violation of their balance indicates a strain of the immune response, contributes to the chronicization and progression of the disease. Patients with different parity have differences in the cytokine type of regulation of the immune response.